Tingkat Kejadian Aeromonasis pada Ikan Koi (Cyprinus carpio carpio) yang Terinfeksi Myxobolus koi pada Derajat Infeksi yang Berbeda [ Aeromonasis Incidence Rate In Koi (Cyprinus carpio carpio) That Infected Myxobolus koi At Different Degrees Of Infection ] - Gunanti Mahasri; Riris Ulfiana; Hari Suprapto (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Myxobolus infection in koi fish allows followed by opportunistic microorganisms infection. Aeromonas hydrophila bacteria classified as opportunistic because it can cause illness in certain condition such as when environmental conditions change, stress and the condition of the host that has been infected by the parasite. This study purpose to determine the incidence rate Aeromonasis in koi (Cyprinus carpio carpio) infected Myxobolus koi at different degrees of infection. The results showed that of 120 samples taken, infected with M. koi in a mild degree of infection is 68.3%. Furthermore the medium infection is 22.5%, 1.7% severe infection and uninfected fish 7.5%. Each level of infection of M. koi taken samples for examination bacteria with skin samples and water. The results of bacterial examination showed that 17 positive samples of fish infected with A. hydrophila (85%) from 20 fish sample. 17 positive samples of fish infected with A. hydrophila consist of 3 sample normal fish, 7 sample M. koi mild infection, 6 sample M. koi medium infection and 1 sample severe infection. The results showed that the fish infected or not infected with M. koi, positive with A. hydrophila infection that needs to be done by using a bacterial colony calculation method of determining the Angka Lempeng Total (ALT) or Total Plate Count (TPC). The calculation results from the number of bacterial colony in various levels of infection of M. koi are sample 1 (normal koi fish) of 1.15 x108 CFU/ml, sample 2 (koi fish with a mild infection of M. koi) as much as 1.3 x108 CFU/ml. While the sample 3 (koi fish with a medium infection of M. koi) 2.02 x108 CFU/ml and sample 4 (with the severe infection of M. koi) 2.60 x108 CFU/ml.